1994
DOI: 10.1177/00220345940730021401
|View full text |Cite
|
Sign up to set email alerts
|

A Re-analysis of Caries Rates in a Preventive Trial using Poisson Regression Models

Abstract: The analysis of caries incidence in clinical trials has several challenging features: (1) The distribution of the number of caries onsets per patient is skewed, with the majority of patients having few or no cavities; (2) the number of surfaces at risk varies (i) over time and (ii) between patients, due to eruption and exfoliation patterns, dental diseases, and treatments; (3) surfaces within a patient differ in their caries susceptibility, and (4) caries onsets within a patient are correlated due to shared ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 17 publications
1
58
0
1
Order By: Relevance
“…Rates were estimated by standard epidemiological methods which incorporate the time at risk (Breslow and Day, 1980;Hujoel et al, 1994). Each surface diagnosed as structurally intact at baseline (or which erupted during the study) and which was examined on at least one other examination date was considered at risk for lesion development.…”
Section: Calibration Of Examiners; Examiner Error Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates were estimated by standard epidemiological methods which incorporate the time at risk (Breslow and Day, 1980;Hujoel et al, 1994). Each surface diagnosed as structurally intact at baseline (or which erupted during the study) and which was examined on at least one other examination date was considered at risk for lesion development.…”
Section: Calibration Of Examiners; Examiner Error Analysesmentioning
confidence: 99%
“…If a surface did not develop a cavity between two examinations, the amount of observation time contributed by that surface equaled the time between the two examinations. If the surface developed a lesion during a time interval, it was assumed that the caries onset occurred in the middle of the interval (Hujoel et al, 1994). Thirty-one surfaces coded as having a filling unrelated to caries (WHO code 9) were deleted from the analysis.…”
Section: Calibration Of Examiners; Examiner Error Analysesmentioning
confidence: 99%
“…Um modelo ajustado para idade e indicador de risco de cárie foi usado para testar as diferenças nos valores de densidade de incidência de cárie entre os grupos submetidos ao programa modificado e ao convencional depois de 18 meses de seguimento. Dada as características do desfecho, essa análise foi efetuada empregando-se modelo de regressão de Poisson 18 . A razão da densidade de incidência foi estimada adotando-se p < 0,05 para rejeição da hipótese de nulidade.…”
Section: Métodosunclassified
“…al., 2002), because many cariesprone teeth were left-censored. Since then, survival analysis methods have been applied to reanalyzing the longitudinal caries data in many other clinical trials, too (Hannigan et al, 2001, Hujoel et al, 2003, Baelum et al, 2003. All these large-scale time dependent analyses of caries data have employed fully parametric tooth-specific methods in permanent dentitions.…”
Section: Survival Analysis In Evidence-based Dentistrymentioning
confidence: 99%
“…Survival modeling has mainly used in the renewed statistical treatment of the findings of previous caries trials, the results showing that the differences existed also when using more sophisticated survival analysis. Hujoel et al, (2003) established the benefits of xylitol with Poisson regression models and Hannigan et al, (2001) who reanalyzed the effect of diet and tooth brushing habits by the log-logistic distribution selected for the parametric competing risk models, showed a good fit to the caries data. She concluded that the marginal model approach may be more suitable than the frailty model for multivariate survival data from caries clinical trials, since most of the source of variability is due to different anatomic susceptibilities of the tooth surfaces (caries may be regarded as a local disease in different teeth) rather than to the specific subject -specific frailty (caries is a general disease in caries prone subjects, like is osteoporosis with fractures).…”
Section: Advantages Of Survival Analysismentioning
confidence: 99%